Time‐series analysis of native and non‐native crayfish dynamics in the Thames River Basin (south‐eastern England). Issue 2 (19th July 2013) - Almeida, David; Ellis, Adam; England, Judy; Copp, Gordon H.
ABSTRACT Monitoring is crucial for the conservation of endangered crayfish species as well as for managing and controlling invasive species. Yet, relatively few studies have assessed relationships between native white‐clawed crayfish Austropotamobius pallipes and non‐native signal Pacifastacus leniusculus, narrow‐clawed Astacus leptodactylus, virile Orconectes virilis and red‐swamp Procambarus clarkii crayfishes in freshwater environments at ecologically relevant spatial and temporal scales. Thus, the present study examines the distribution dynamics of native and non‐native crayfishes in the River Thames Basin District (16 133 km2, south‐eastern England) over four decades (1971–2010). To reveal geographical bioinvasion and decline patterns, data on occurrences (sampling site, date) of native white‐clawed and four non‐native crayfishes were used to create sequences of decade maps for each species. Cumulative numbers of occupied grid squares were used to construct 'invasion/decline' curves and rates. To quantify dynamic features, the frequencies of survey occurrence for each species were subjected to time‐series analysis, followed by cross‐correlation to determine relationships between crayfishes. White‐clawed crayfish was initially widespread, but gradually disappeared after the mid‐1970s, coinciding with the introduction and initial dispersal of signal crayfish. During 2001–2010 white‐clawed crayfish numbers declined steeply. Introduced in the mid‐1980s, narrow‐clawed crayfish spread within a few years, but is now restricted to the east of the basin, where virile and red‐swamp crayfishes were reported with low presence since their introductions in 2006. Dynamics of white‐clawed and signal crayfishes showed the opposing trends with a highly significant negative association. Geographical patterns indicate that non‐native crayfishes were introduced in multiple locations in the study area. Recovery of native crayfish seems unlikely, given the impacts of signal crayfish and the continuing arrival of new crayfish species. This paper demonstrates the utility of using broad temporal and spatial scales for revealing accurate insights on invasion and decline dynamics. Copyright © 2013 Crown copyright.